Temporal Lobectomy for Epilepsy with Congenital Porencephaly and Hippocampal Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The clinical characteristics and surgical outcome of 6 patients with intractable epilepsy and coexisting extratemporal porencephaly and hippocampal sclerosis are presented from the University of Alabama, Birmingham, AL.